Signalling in auctions: Experimental evidence - Olivier Bos; Francisco Gomez-Martinez; Sander Onderstal; Tom Truyts (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We study the relative performance of the first-price sealed-bid auction, the second-price sealed-bid auction, and the all-pay sealed-bid auction in a laboratory experiment where bidders can signal information through their bidding behaviour to an outside observer. We consider two different information settings: the auctioneer reveals either the identity of the winning bidder only, or she also reveals the bidders' payments to an outside observer. We find that the all-pay sealed-bid auction in which the bidders' payments are revealed outperforms the other mechanisms in terms of revenue, while this mechanism underperforms in terms of efficiency relative to the winner-pay auctions.
Keywords: C92; D44; D82; 330; Auctions; Signalling; Experiments